MANAJEMEN STRATEGIS KEPALA SEKOLAH DALAM PERENCANAAN BERBASIS DATA DI SD - Seni Fitriani; Eva Dianawati Wasliman (MANAJERIAL : Jurnal Inovasi Manajemen dan Supervisi Pendidikan, 2026)
ABSTRAKThe transformation of education policy through the Merdeka Belajar Program, the National Assessment, and the use of the Education Report positions Data-Based Planning (PBD) as a key instrument for improving school quality. At the same time, the principal is positioned as a strategic actor who drives the functions of planning, organizing, actuating, and controlling in school management, as widely discussed in educational management literature. However, in practice particularly in public elementary schools PBD is still often perceived as an administrative obligation focused on document compliance, and therefore has not been fully integrated into the principal’s strategic management, as also reported in various studies. This study analyzes the principal’s strategic management of PBD to enhance school performance and effectiveness at SDN Loa 1, Paseh District. Using a qualitative approach with an intrinsic case study design, the participants included the principal, teachers involved in the planning team, and a purposively selected representative of the school committee. Data were collected through in-depth interviews, participant observation, and document analysis (Education Report, RKJM, RKT, and RKAS), and were analyzed using Miles and Huberman’s interactive model. The findings indicate that the principal has initiated PBD implementation through school quality profile analysis and the formulation of priority programs, yet data use remains concentrated on learning outcome indicators. POAC functions are evident, but are not fully supported by teachers’ data literacy and an adequate data documentation system as also indicated by previous studies. Transformasi kebijakan pendidikan melalui Program Merdeka Belajar, Asesmen Nasional, dan pemanfaatan Rapor Pendidikan menempatkan Perencanaan Berbasis Data (PBD) sebagai instrumen utama peningkatan mutu satuan pendidikan. Kepala sekolah diposisikan sebagai aktor strategis yang menggerakkan fungsi perencanaan, pengorganisasian, pelaksanaan, dan pengendalian dalam pengelolaan sekolah, sebagaimana banyak dibahas dalam kajian manajemen pendidikan. Namun, di sekolah dasar negeri PBD masih kerap dipahami sebagai kewajiban administratif yang berorientasi pada pemenuhan dokumen, sehingga belum sepenuhnya terintegrasi dalam manajemen strategis, sebagaimana juga ditemukan dalam berbagai kajian. Penelitian ini menganalisis manajemen strategis kepala sekolah dalam pengelolaan PBD melalui kerangka POAC untuk meningkatkan kinerja dan efektivitas sekolah di SDN Loa 1 Kecamatan Paseh. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik. Subjek meliputi kepala sekolah, guru tim perencanaan, dan perwakilan komite sekolah yang dipilih secara purposif. Data dikumpulkan melalui wawancara, observasi, dan studi dokumentasi (Rapor Pendidikan, RKJM, RKT, RKAS), lalu dianalisis dengan model interaktif Miles dan Huberman. Hasil menunjukkan implementasi PBD telah berjalan melalui analisis profil mutu dan penetapan program prioritas, tetapi pemanfaatan data masih dominan pada indikator hasil belajar. Fungsi POAC tampak, namun belum ditopang literasi data guru dan sistem dokumentasi yang memadai sebagaimana ditunjukkan dalam penelitian sebelumnya.